Pelaksanaan Bimbingan Belajar Siswa-Siswi SDK Kekandere 2 - Bantas, Maria Goretty Diciloam; Suryani, Lely; Dhiki, Yasinta Yenita; Taga, Gregorius; Aje, Ariswan Usman; Sannar, Donatus; Paresa, Yoseph Delsony; Sarong, Lydia; Bay, Ernesta (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2023)
Education is one thing that cannot be separated from life, both formally and informally and school is one of the facilities for obtaining an education. However, with a large number of students in one class, the teacher cannot guide students one by one. Likewise, the large number of subjects that must be studied every day makes it difficult for students to remember all the lessons given by the teacher, so students still need study guidance outside of school. This service is carried out to help develop learning and discover the learning habits of elementary school students in grades 4, 5 and 6 at Kekandere 2 Nangapanda Elementary School. The method of implementing tutoring is to compile and design a guidance program for students during the learning process in class and group tutoring in the afternoon to increase students' understanding of mathematics by providing continuous practice questions based on the mathematics subject matter that has been studied in the school environment. The results of this study were to provide good results for students in mathematics as seen from the enthusiasm of students in solving math problems and the effect on the daily test scores carried out by the teacher during the learning process